A Research Study of Imam Al-Sakhawi’s Methodology and Style in Al-Maqasid Al-Hasanah: المقاصد الحسنتہ میں امام سخاوی کے منہج و اسلوب کا تحقیقی مطالعہ - Ali, Dr. Rizwan; ur Rehman, Dr. Syed Mujeeb (Al Khadim Research Journal of Islamic Culture and Civilization, 2024)
Hadith is the second most important source of Islamic Law. MUHADDITHIN have tried to secure this source by compiling proper books regarding Prophetic sayings and biography of narrators of Hadiths as well. Similarly, they also tried their best to collect and arrange in shape of books all the sentences and Hadiths which were common among the people of different classes. Some of which were authentic and some were ZA`IF or MAUZU`. Such books are known among the Islamic scholars as KUTUBU AL AHADITH AL MUSHTAHARAH and IMAM SAKHAVIY’s Book AL MAQASID AL HASANAH is the most important book among these books. In this article, an attempt will be made to make clarification about AL AHADITH AL MUSHTAHARAH and methodology of IMAM SAKHAVIY in AL MAQASID AL HASANAH will also be discussed in detail.